Physico-chemical and Bio-chemical Studies of Some Organoruthenium(II) Complexes with Mixed Ligand Physiologically Active Substituted Quinazole-4-one - NAND MISHRA, BHASKARA; KUMAR, PRABHAT; SHARMA, R.N. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of ruthenium chelate of oxygen, nitrogen and sulphur containing ligand 2-mercapto-3-phenyl quinazole-4-one having general formula (RuH(Z)(PΦ3)n (QPMTH)m Cl] (where Z = CO/CS, if n =1 or 2 and then m = 2 or 1, QPMTH = 2-mercapto-3-phenyl quinazole-4-one) have been prepared and characterized by IR, UV spectral data, magnetic and conductance measurements. IR spectra of complexes suggest the coordination of ligand through sulphur atom and PΦ3, CS and CO are present as secondary ligands in complextion. UV spectral data and magnetic moment values of the complexes suggest octahedral geometry and molar conductance values of the complexes support their non-electrolytic nature.